If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5y + 1) + -1(-4y + -4) = 2 Reorder the terms: -1(1 + 5y) + -1(-4y + -4) = 2 (1 * -1 + 5y * -1) + -1(-4y + -4) = 2 (-1 + -5y) + -1(-4y + -4) = 2 Reorder the terms: -1 + -5y + -1(-4 + -4y) = 2 -1 + -5y + (-4 * -1 + -4y * -1) = 2 -1 + -5y + (4 + 4y) = 2 Reorder the terms: -1 + 4 + -5y + 4y = 2 Combine like terms: -1 + 4 = 3 3 + -5y + 4y = 2 Combine like terms: -5y + 4y = -1y 3 + -1y = 2 Solving 3 + -1y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = 2 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 2 + -3 -1y = 2 + -3 Combine like terms: 2 + -3 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1
| 3/8x-1/3x-1/6x=-6 | | 5x-9y-7x+6y= | | X/7-4=-8 | | 7x=-2y | | 12(4x-7)=4(12x+2) | | 17-0.3(g-3)=0.1(2g-3) | | (3)(7)(8)= | | [7(c+5)-17]+[2(c-3)+5]= | | (2)(8)(7)= | | 9+2n-1=6n+15-3n | | 2ln(x-5)=1 | | (1.95)(7.50)(7.35)= | | (1.94)(7.51)(7.34)= | | c=(2)(3.14)r | | 0.3X-0.7X-3=1 | | 32/9+91/4 | | 5+19y-2=9y+78-5y | | 2/9+1/4 | | -4(3b+1)+(13b-3)=0 | | 3(2y+4)-42=-1(12y-24) | | -8/x=6 | | (-2)(3)(x)= | | 2(3x-6)=43 | | 1(t-3)+7t=4(2t+5)-12 | | 3.6x=2.6x+9.0 | | 7x-13=-97 | | -(3y+2)-(-2y-8)=-1 | | 13x+8-5=12x-2 | | 9-5x=6x+9 | | 3l/4=7 | | 4.5q-5.7-4.2q=0.7q-3.2 | | 8x+10x=152.5 |